Analytical design technique for real‐to‐real single‐ and dual‐frequency impedance matching networks in lossy passive environment. Issue 6 (20th March 2018) - A.R., Aravinth Kumar; Singh, Shiv Govind; Dutta, Ashudeb
Abstract : A passive‐loss accounted analytic design technique for impedance matching networks is proposed here for efficient radio frequency (RF) circuit design. The impact of component losses on matching performance is briefed initially. To overcome the matching impact due to component losses, a set of modified equations are introduced which finds the accurate inductor and capacitor values accounting component losses. The proposed technique is applied for single‐frequency L‐match, Pi‐match, T‐match and dual‐frequency L‐match networks. The improvement in matching performance by using the proposed design technique is validated through simulations and measurements in UMC 0.18 µm complementary metal oxide semiconductor technology. The measurement results closely (90–95%) follow ideal component performance. Hence, the proposed passive‐loss accounted design technique will be more useful in accurate low power RF circuit design.